4A.10: PREFERENTIAL REDUCTION IN MORNING/NOCTURNAL HYPERTENSION BY RENAL DENERVATION FOR DRUG- RESISTANT HYPERTENSION. (June 2015) - Kario, K.; Bakris, G.L.; Bhatt, D.
Abstract : Objective: To study the impact of catheter-based renal artery denervation (RDN) on change in morning and night systolic BP (SBP) defined by ambulatory BP measurements (ABPM) 6 months post-randomization. Design and method: SYMPLICITY HTN-3 and SYMPLICITY HTN-Japan are prospective, randomized, controlled trials of RDN for treatment of resistant hypertension. However, SYMPLICITY HTN-3 included a blinded, sham control and HTN-Japan control patients were not blinded and continued medical management alone. Patients in both trials were on a stable antihypertensive regimen of at least 3 drugs including a diuretic before randomization. Average morning SBP (7 am to 9 am), maximum morning SBP (between 6 am and 10 am), average nocturnal SBP (1 am to 6 am), average peak nocturnal SBP (average of 3 highest SBPs between 1 am and 6 am) and average daytime SBP were calculated using pooled patient-level ABPM data. Six-month change in SBP parameters were compared between RDN and control patients. Results: A total of 386 patients (364 from HTN-3 and 22 from Japan) received RDN and 190 patients were in the control group (171 from HTN-3 and 19 from Japan). The average morning SBP was reduced -8.0 ± 22.3 mmHg in the RDN group which was significantly more than the change in the control group (-3.5 ± 22.2 mmHg, p = 0.023). The maximum morning SBP change was -8.6 ± 22.3 mmHg for RDN patients and -4.8 ± 23.8mmHg for controls (p = 0.072). Furthermore, the change in average nocturnal and average peak nocturnal SBP was significantly greater in the RDN patients compared with the control patients; -6.3 ± 18.1 vs -1.7 ± 19.2 mmHg, p = 0.008 for average nocturnal SBP and -6.7 ± 20.0 vs -1.3 ± 20.5 mmHg, p = 0.004 for average peak nocturnal SBP. Average daytime SBP change was not significantly between the RDN and control groups (-7.1 ± 16.0 vs -5.7 ± 18.0 mmHg, p = 0.349). Conclusions: This analysis demonstrated that RDN significantly reduced morning and nighttime SBP compared with control patients suggesting potential benefit of this device approach on cardiovascular protection in drug-resistant hypertension when measurements are captured during higher risk time periods.